2009
DOI: 10.1007/s10267-008-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizae and ectomycorrhizal fungal fruit bodies in pine stands differentially damaged by pine wilt disease

Abstract: We surveyed ectomycorrhizae, ectomycorrhizal fungal fruit bodies, and soil physical properties in one heavily damaged and two lightly damaged pine stands on Mt. Tsukuba, central Japan. The rate of ectomycorrhizal root tips was not different between heavily and lightly damaged pine stands. For ectomycorrhizae, Cenococcum geophilum had high relative abundance in the heavily damaged pine stand. The number of ectomycorrhizal fungal fruit bodies in the heavily damaged pine stand was much lower than that in the ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Under natural conditions, PWD interference can alter the composition and diversity of fungal communities (Akema and Futai, 2005;Ugawa et al, 2009;Chu et al, 2016Chu et al, , 2018Nakashima et al, 2016) and bacteria (Mabuhay and Nakagoshi, 2012;Shi et al, 2015) in pine forests. Using DGGE, we analyzed the effects of PWN infection on the diversity and community structure of rhizosphere fungi and bacteria in the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…Under natural conditions, PWD interference can alter the composition and diversity of fungal communities (Akema and Futai, 2005;Ugawa et al, 2009;Chu et al, 2016Chu et al, , 2018Nakashima et al, 2016) and bacteria (Mabuhay and Nakagoshi, 2012;Shi et al, 2015) in pine forests. Using DGGE, we analyzed the effects of PWN infection on the diversity and community structure of rhizosphere fungi and bacteria in the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…Ectomycorrhizae formed by Astraeus sp., Atheliaceae, Boletaceae, and Thelephoraceae of pine seedlings showed the highest survival and growth rates regardless of the variety of black pine [32]. However, Ugawa et al, (2009) showed that the rates of ectomycorrhizal root tips were similar between heavily and lightly damaged pine stands, but a higher number of ECMF sporocarp and lower relative abundance of Cenococcum geophilum Fr. were observed in the lightly damaged pine stands [36].…”
Section: Introductionmentioning
confidence: 92%
“…However, Ugawa et al, (2009) showed that the rates of ectomycorrhizal root tips were similar between heavily and lightly damaged pine stands, but a higher number of ECMF sporocarp and lower relative abundance of Cenococcum geophilum Fr. were observed in the lightly damaged pine stands [36]. In addition, our previous study found that PWD could alter the community of root-associated fungi and reduce the colonization rate of ECMF and DSE [14,16].…”
Section: Introductionmentioning
confidence: 93%
“…However, the rates of ectomycorrhizal root tips were not different between heavily and lightly damaged pine stands in the study of Ugawa et al . (), although Cenococcum geophilum had high relative abundance and the number of ECMF fruiting bodies was much lower in the heavily damaged pine stand. The symbiotic function of ectomycorrhizae differs among fungal species (Nara ).…”
Section: Introductionmentioning
confidence: 94%